De novo diffuse large B‐cell lymphoma with a CD20 immunohistochemistry‐positive and flow cytometry‐negative phenotype: Molecular mechanisms and correlation with rituximab sensitivity. Issue 1 (22nd December 2013) - Tokunaga, Takashi; Tomita, Akihiro; Sugimoto, Keiki; Shimada, Kazuyuki; Iriyama, Chisako; Hirose, Tatsuya; Shirahata‐Adachi, Mizuho; Suzuki, Yasuhiro; Mizuno, Hiroki; Kiyoi, Hitoshi; Asano, Naoko; Nakamura, Shigeo; et al.
<x xml:space="preserve">Abstract</x> CD20 is expressed in most B‐cell lymphomas and is a critical molecular target of rituximab. Some B‐cell lymphomas show aberrant CD20 expression, and rituximab use in these patients is controversial. Here we show both the molecular mechanisms and the clinical significance of de novo diffuse large B‐cell lymphomas (DLBCL) that show a CD20 immunohistochemistry (IHC)‐positive and flow cytometry (FCM)‐ negative (IHC[+]/FCM[−]) phenotype. Both IHC and FCM using anti‐CD20 antibodies L26 and B1, respectively, were analyzed in 37 of the 106 cases of de novo DLBCL; 8 (22%) of these cases were CD79a(+)/CD20(+) with IHC and CD19(+)/CD20(−) with FCM. CD20 (MS4A1) mRNA expression was significantly lower in IHC(+)/FCM(−) cells than in IHC(+)/FCM(+) cells (P = 0.0005). No genetic mutations were detected in MS4A1 promoter and coding regions. Rituximab‐mediated cytotoxicity in the CDC assay using IHC(+)/FCM(−) primary cells was significantly lower than in IHC(+)/FCM(+) cells (P < 0.05); however, partial effectiveness was confirmed. FCM using rituximab detected CD20 more efficiently than B1. No significant difference was observed between IHC(+)/FCM(−) and IHC(+)/FCM(+) patients in overall survival (P = 0.664). Thus, lower expression of CD20 mRNA is critical for the CD20 IHC(+)/FCM(−) phenotype. Lower CD20 expression with FCM does not rule out rituximab use in these patients if expression is confirmed with IHC. FCM using rituximab may be more informative than B1 for predicting rituximab effectiveness in IHC(+)/FCM(−) cases.